Interaksi simbolik pengguna aplikasi dating online bumble di Indonesia (Faculty of Communications Science, Dr. Soetomo University, 2021)
In this era of technological development, social media provides convenience in social interactions that affect social relationships. From making new friends, work relationships to finding a partner. During this pandemic, online dating is chosen as an alternative to finding a partner, whether for a serious relationship or just looking for friends. Bumble is an alternative virtual dating that can be used to make a close friend from cyberspace. The aims of this research to find out how communication is built to create an impression through the meaning of text messages in order to get a match or communication participant. This research uses a descriptive qualitative method with a case study approach. The result of this research is that the communication activities carried out by informants to build an impression on their